2013
DOI: 10.1097/brs.0b013e3182a62527
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications and Mortality After Spinal Fusions

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…[7][8] Regardless of the reason, during fiscal year 2013, the Medicare program reimbursed hospitals over $3.6 billion for spinal fusion surgery, making total spending on spinal fusion surgery one of the three highest admission outlays in the Medicare program; along with total knee arthroplasty and congestive heart failure. 9 A number of articles have reported on mortality and selected adverse events associated with patients undergoing spinal fusion surgery [10][11][12][13][14] and other studies have examined length of stay 8,15 and unplanned readmission after spinal surgery. [16][17] However, only a few of these studies used a national sample of spinal surgery patients in the United States 8,11,[13][14][15] each adverse event.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] Regardless of the reason, during fiscal year 2013, the Medicare program reimbursed hospitals over $3.6 billion for spinal fusion surgery, making total spending on spinal fusion surgery one of the three highest admission outlays in the Medicare program; along with total knee arthroplasty and congestive heart failure. 9 A number of articles have reported on mortality and selected adverse events associated with patients undergoing spinal fusion surgery [10][11][12][13][14] and other studies have examined length of stay 8,15 and unplanned readmission after spinal surgery. [16][17] However, only a few of these studies used a national sample of spinal surgery patients in the United States 8,11,[13][14][15] each adverse event.…”
Section: Introductionmentioning
confidence: 99%
“…Goz and coworkers indicated that the mortality rates after spine surgery remained constant over a 10-year period. 9 Thoracic spine surgery had the highest death incidence (1.2%), followed by cervical (0.46%) and lumbar (0.14%). A similar pattern was observed in another database study, with the mortality incidence being 0.57%, 0.13%, and 0.11% for the thoracic, cervical, and lumbar regions, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…[12-14] Such studies have found that age and comorbidity burden of patients undergoing spinal fusion has increased over the last decade. [12] However, the effects of age, specific comorbidities, and hospital characteristics on outcomes immediately following atlantoaxial fusion have not yet been quantified. Identifying and quantifying predictors of postoperative outcome can improve patient risk counseling for atlantoaxial fusion.…”
Section: Introductionmentioning
confidence: 99%